Rapid in vitro selection of human immunodeficiency virus type 1 resistant to 3'-thiacytidine inhibitors due to a mutation in the YMDD region of reverse transcriptase. - Tisdale, M (1993)
Resistant variants of human immunodeficiency virus type 1 (HIV-1) have been selected by limited passage in MT4 cells of both wild-type and 3'-azido-3'-deoxythymidine (AZT, zidovudine)-resistant strains with the nucleoside analogues (-)-2'-deoxy-3'-thiacytidine (3TC) and (-)-2'-deoxy-5-fluoro-3'-thiacytidine (FTC). Virus variants selected independently were crossresistant to both inhibitors. This rapid in vitro selection of resistant virus has not previously been seen with nucleoside analogues but is reminiscent of that observed with the nonnucleoside reverse transcriptase inhibitors. However, passage of wild-type virus with a combination of AZT and FTC appreciably delayed emergence of FTC-resistant virus. DNA sequence analysis of the reverse transcriptase coding region from FTC-resistant virus revealed changes at codon 184 in the highly conserved Tyr, Met, Asp, Asp (YMDD) region. When the mutation Met184-->Val was introduced into the infectious clone HXB2, this change alone accounted for the resistance (> 1000-fold) seen with both 3TC and FTC, and for a 5- to 15-fold reduction in sensitivity to their (+) enantiomers. It had no effect on susceptibility to AZT or nevirapine and minimal effect on susceptibility to 2',3'-dideoxyinosine and 2',3'-dideoxycytidine. To determine the influence of this mutation in a background of mutations conferring resistance to AZT and nonnucleoside reverse transcriptase inhibitors, a series of HIV-1 variants were created by site-directed mutagenesis. All mutants with Met184-->Val were cross-resistant to 3TC and FTC. The Met184-->Val mutation did not influence nevirapine resistance, but resistance to AZT was suppressed. Similar suppression of AZT resistance was seen with Tyr181-->Cys. Interestingly, when both Met184-->Val and Tyr181-->Cys substitutions were present, highly resistant virus reverted to complete AZT sensitivity. Assessment of the interactive effects of multiple drug-resistance mutations may help to establish a rationale for using these drugs in the future therapy of HIV disease.